PENGARUH PENERAPAN GCG, LEVERAGE DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DAN REAL ESTAT YANG TERDAFTAR DI BEI TAHUN 2021-2024 - Fitri, Eka; Amalia, Wia Rizqi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research was conducted to find out and analyze the Board of Commissioners, Audit Committee, Institutional Ownership, and Managerial Ownership, Leverage (Debt to Equity Ratio / DER), and Financial Performance (ROA) to Company Value (PER). The population of this study is Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. Through the use of purposeful sampling, the research sample consisted of 20 companies. According to the findings, Company Value is adversely impacted by Managerial Ownership and Debt to Equity Ratio, while Return on Assets (ROA) has a favorable impact. The Board of Commissioners, Audit Committee, and Institutional Ownership, on the other hand, have little impact on the value of the business. These results show that leverage and certain other GCG mechanisms have not been able to genuinely contribute to the company's value, but that some financial performance and Good Corporate Governance mechanisms have significantly impacted investor perception.